Virtuous profits: Pay for success arrangements and the future of recidivism reduction. (April 2018) - Myers, Randolph R.; Goddard, Tim
Pay for success contracting is the latest financial instrument for funding social programs. Governments in Australia, the UK, the US, and elsewhere are piloting their use in reentry programs, youth offender programs, and a host of other initiatives aimed at homelessness, child welfare, workforce development, and preventive health care. Under a pay for success arrangement, private investors put up capital to fund a program, and if successful, a government agency will repay the investors with a yield, that is, with a profit. This article situates pay for success contracting in the context of reentry and decarceration and it theorizes how the arrangement will reverberate through new alternatives to incarceration and fundamentally change the meaning of "what works." The article concludes by locating pay for success within the broader drift toward securitizing marginal populations under neoliberalism.